Effective thermal conductivity of nanofluids - A new model taking into consideration Brownian motion - Shukla, Kedar N.; Koller, Thomas Manfred; Rausch, Michael Heinrich; Fröba, Andreas Paul (International Journal of Heat and Mass Transfer, 2016)
In this study, a new analytical model for the effective thermal conductivity of liquids containing dispersed spherical and non-spherical nanometer particles was developed. In addition to heat conduction in the base fluid and the nanoparticles, we also consider convective heat transfer caused by the Brownian motion of the particles. For nanoparticle suspensions, the latter mechanism has significant influence on the effective thermal conductivity, which is reduced compared to a system in which only conduction is considered. The simple model developed allows for the prediction of the effective thermal conductivity of nanofluids as a function of volume fraction, diameter, and shape of the nanoparticles as well as temperature. Due to the inconsistency of experimental data in the literature, the model has been compared with the established Hamilton-Crosser model and other empirical models for the systems aluminum oxide (Al2O3) and titanium dioxide (TiO2) suspended in water and ethylene glycol. The theoretical estimates show no anomalous enhancement of the effective thermal conductivity and agree very well with the Hamilton-Crosser model within relative deviations of less than 8% for volume fractions of spherical particles up to 0.25. In accordance with the Hamilton-Crosser model for non-spherical particles, our model reveals that a more distinct increase in the enhancement of the effective thermal conductivity can be achieved using non-spherical nanoparticles having a larger volume-specific surface area. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Effective thermal conductivity; Modeling; Nanofluids; Nanoparticles